Pemodelan Curah Hujan-Limpasan Pada Sub DAS Cikapundung Hulu - Ika Sari Damayanthi Sebayang; Syaefudin Wibowo (FORUM MEKANIKA, 2020)
The Cikapundung River is one of the rivers that divides the city of Bandung and is often used as the main drainage center of the city, the flow of sewage or waste, tourism objects, and raw water sources. This causes the importance of observing reliable discharge values flowing on the Cikapundung River. In this study the authors analyzed the availability of minimum river discharge in Cikapundung Hulu Sub Das using the FJ Mock method. This study uses rainfall data and climatology data. The rainfall data used are rainfall data from Dago Pakar station and Meteo Lembang station, with a span of 10 years while the climatological data used is data from the Bandung Geophysical Station with a span of 10 years. Mainstay discharge calculated using the F.J Mock Method, where in the F.J Mock calculation there are a number of parameters assumed. This modeling test process is by calibrating the parameters assumed by Trial and Error. The average discharge magnitude for Q50, Q80, Q90, and Q95 in calculating the mock model in the period 2008 to 2014 resulted in a value of 3.87 m³ / sec; 2.98 m³ / sec; 2.46 m³ / sec; and 2.21 m³ /sec. While the discharge values of Q50, Q80, Q90, and Q95 in the observation debit produce successive values of 3.85 m³ / sec; 2.45 m³ / sec; 2.05 m³ / sec; and 1.91 m³ / sec. Even with the increase in the calculation period, reliable debit values have a tendency to rise.